Sources of Life Strengths Appraisal Scale: A Multidimensional Approach to Assessing Older Adults’ Perceived Sources of Life Strengths - Prem S. Fry; Dominique L. Debats (Journal of Aging Research)
Both cognitive and psychosocial theories of adult development stress the fundamental role of older adults’ appraisals of the diverse sources of cognitive and social-emotional strengths. This study reports the development of a new self-appraisal measure that incorporates key theoretical dimensions of internal and external sources of life strengths, as identified in the gerontological literature. Using a pilot study sample and three other independent samples to examine older adults’ appraisals of their sources of life strengths which helped them in their daily functioning and to combat life challenges, adversity, and losses, a psychometric instrument having appropriate reliability and validity properties was developed. A 24-month followup of a randomly selected sample confirmed that the nine-scale appraisal measure (SLSAS) is a promising instrument for appraising older adults’ sources of life strengths in dealing with stresses of daily life’s functioning and also a robust measure for predicting outcomes of resilience, autonomy, and well-being for this age group. A unique strength of the appraisal instrument is its critically relevant features of brevity, simplicity of language, and ease of administration to frail older adults.